State-Level Efforts to Transfer Manufacturing Technology: A Survey of Programs and Practices - Wyckoff, Andrew W.; Tornatzky, Louis G. (Management Science, 1988)
This study analyzed state-level university-based efforts to increase manufacturing productivity through the transfer of technologies, such as robotics and microcomputers, to manufacturing establishments. A survey was conducted by phone interview of 15 state programs that were operating in 1985. Information was gathered on the goals, planning, budgets, marketing, staffing, organizational structure, technical focus, and evaluation practices of the programs. All of the programs were university-based, typically attached to the engineering schools of land grant public universities. Programs generally fell into three types: (1) active programs, which included activities that ranged from technology needs assessment to consultation assistance; (2) broker programs, which provided limited direct assistance, but put industrial clients in touch with people who could; and (3) passive programs, which focused on providing information services, such as data base searches. Major issues of development and operation of the programs included: conflicts with the academic context, difficulties in keeping technically up to date and problems in retaining quality staff. A significant strategic and program design issue was how to balance intensive and specialized services with the need to respond to the heterogeneous needs of a broad clientele. Few of the programs had adequate planning and evaluation, perhaps contributing to their difficulties.